Self-awareness of Makassar city football athletes on facing the 17th provincial sports week 2022 - Hasyim, Hasyim; Sulaeman, Sulaeman (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
This study aims to see the self-awareness of Makassar City Football athletes through their ability to maintain physical condition ahead of the 17th Provincial Sports Week in 2022. This type of research is cross sectional. The population in this study were all athletes from Makassar City who took part in the 17th South Sulawesi Provincial Sports Week. While the sample in this study were athletes from the Makassar City football team who would take part in the South Sulawesi Provincial Sports Week, who were selected through a purposive sampling technique. The data collection technique in this study was a physical condition test. The physical elements measured are flexibility, strength, coordination, power, muscle endurance, speed, agility, and general endurance. The results of the analysis show that 21 athletes fall into the good category with a percentage of 91.3 percent of the total sample. 3 samples are in the medium category with a percentage of 8.7 percent of the total sample. While there were no athletes who were in the very good category, the less category, or the very poor category. So, it can be concluded that based on the results of the research and discussion stated earlier, it can be concluded that "The self-awareness of the Makassar City Football Player athletes in facing the 17th Provincial Sports Week is at high self-awareness". This is evidenced by the physical condition of the players who are above average. Key words: Self Awareness, Football, Physical Condition